A garantia da convivência familiar e comunitária : desafios postos ao programa de acolhimento familiar na Região das Missões - Aloraldo, Vanelise de Paula (2017)
This study discusses the Family Warm-Up Program in the Missions Region based on the experience that has been developed in the municipality of Santo Ângelo / RS through a partnership between the public policy of Social Assistance and the Judiciary. Therefore, it is based on the analysis of how those involved in this process comprise this Service that makes up the Special Social Protection of High Complexity. It was researched how this Program was implemented and how it is organized to meet this protection measure; Such as the extended family, the welcoming families and the technical staff realize that this type of reception is being developed, which represents an alternative to institutionalization. In order to get these answers, we chose as a methodological approach the research under mixed focus and for the analysis of the data collected - through interviews with semi-structured forms applied to nine (9) subjects (six (6) One (1) extended family and (2) staff of the technical team) and a systematic and documentary observation route made possible by three (3) pioneering agents ((1) a coordinator, (1) a social assistance secretary, and Judge) - the analysis of content according to Bardin (1977) in the light of the Materialist Historical Dialectic Method. The research was carried out at the headquarters of the Family Warm-Up Program and in the homes of families that temporarily shelter children and adolescents who were separated from the original family by judicial means. Reception services were considered to have segregated the hosted public for a long time, distancing them from their communities, depriving them of their freedom through hospitalization, offering no references of support in the institutions to the turnover of professionals and hardly welcoming them (according to the legislation), making it impossible for the family to live together. It is pointed out in this study the family reception as a possibility to guarantee fundamental rights historically neglected by the other reception modalities. It is evident the need to unite efforts, investing and directing the professional action of the teams to preserve the existing links with the extended family. In this sense, it is pointed out that the Program allows that links can be strengthened and, in addition, new ones are formed. It is warned that much more must be invested and directed the professional action of the teams and the intersectoral network for constant qualification of the families that they host, as well as orientation and social and family support to the definitive families. It was found, through the present research, that some experiences can generate good results so that the family and community coexistence is effectively guaranteed.